Morphology and dielectric properties of single sample Ni0.5Zn0.5Fe2O4 nanoparticles prepared via mechanical alloying - Hassan, Rafidah; Hassan, Jumiah; Hashim, Mansor; Paiman, Suriati; Azis, Raba’ah Syahidah (Springer, 2014)
Nickel-zinc ferrite nanoparticles are important soft magnetic materials for high and low frequency device application and good dielectric materials. Nickel-zinc ferrite nanoparticles with composition Ni0.5Zn0.5Fe2O4 were prepared using mechanical alloying to analyze the effect of sintering temperature on microstructure evolution of a single sample with dielectric properties. The single sample with nanosized pellet was sintered from 600 °C to 1200 °C and analyzed by X-ray diffraction (XRD) to investigate the phases of the powders and by field emission scanning electron microscopy (FESEM) for the morphology and microstructure analyses. Dielectric properties such as dielectric constant (ɛ′) and dielectric loss (ɛ″) were studied as functions of frequency and temperature for Ni0.5Zn0.5Fe2O4. The dielectric properties of the sample were measured using HP 4192A LF impedance analyzer in the low frequency range from 40 Hz to 1 MHz and at temperature ranging from 30 °C to 250 °C. The results showed that single phase Ni0.5Zn0.5Fe2O4 cannot be formed by milling alone and therefore requires sintering. The crystallization of the ferrite sample increased with increasing sintering temperature, while the porosity decreased and the density and average grain size increased. Evolution of the microstructure resulted in three activation energies of grain growth, where above 850 °C there was a rapid grain growth in the microstructure. Dielectric constant and loss factor decreased with the increase in frequency. The optimum sintering temperature of Ni0.5Zn0.5Fe2O4 was found to be 900 °C which had high dielectric constant and low dielectric loss.